The Effect of Work Motivation and Work Facilities on Employee Performance at Magic Star Printing in Surabaya - Monica Diah Abilia; Bayu Airlangga Putra; Hermien Tridayanti; Elok Damayanti (Journal of World Conference (JWC), 2021)
The purpose of this research to analyze the effect of motivation and work facilities on employee performance at Magic Star Printing in Surabaya. This study uses a quantitative descriptive method. The population of this study was 48 respondents. The results of the study using the t test showed a positive effect of 0.002 < 0.05. So that the hypothesis of work motivation has a significant partial effect on employee performance at the Surabaya Magic Star Printing. The results of the study using the t test showed a positive effect of 0.002 < 0.05. So that work facilities have a significant partial effect on work facilities on employee performance at Magic Star Printing in Surabaya. The results of the F test showed a positive effect of 0.000 <0.05. It can be said that work motivation and work facilities have a significant effect on the performance of Magic Star Printing employees in Surabaya.